Effects of adipose-derived stromal cells and endothelial progenitor cells on adipose transplant survival and angiogenesis. - Fengshan Gan; Liu Liu; Qingzhu Zhou; Wenli Huang; Xinwei Huang; Xian Zhao (PLoS ONE, 2022)
Background A paracrine mechanism is thought to mediate the proangiogenic capacity of adipose-derived stromal/stem cells (ASCs). However, the precise mechanism by which ASCs promote the formation of blood vessels by endothelial progenitor cells (EPCs) is unclear. Methods The EPCs-ASCs cocultures prepared in different ratios were subjected to tube formations assay to verify whether ASCs could directly participate in the tube genesis. The supernatant from cultured ASCs was used to stimulate EPCs to evaluate the effects on the angiogenic property of EPCs, as well as capacity for migration and invasion. A coculture model with transwell chamber were used to explore the regulation of angiogenesis markers expression in EPCs by ASCs. We then mixed ASCs with EPCs and transplanted them with adipose tissue into nude mice to evaluate the effects on angiogenesis in adipose tissue grafts. Results In the EPCs-ASCs cocultures, the tube formation was significantly decreased as the relative abundance of ASCs increased, while the ASCs was found to migrate and integrated into the agglomerates formed by EPCs. The supernatant from ASCs cultures promoted the migration and invasion of EPCs and the ability to form capillary-like structures. The expression of multiple angiogenesis markers in EPCs were significantly increased when cocultured with ASCs. In vivo, ASCs combined with EPC promoted vascularization in the fat transplant. Immunofluorescence straining of Edu and CD31 indicated that the Edu labeled EPC did not directly participate in the vascularization inside the fat tissue. Conclusions ADSC can participate in the tube formation of EPC although it cannot form canonical capillary structures. Meanwhile, Soluble factors secreted by ASCs promotes the angiogenic potential of EPCs. ASCs paracrine signaling appears to promote angiogenesis by increasing the migration and invasion of EPCs and simultaneously upregulating the expression of angiogenesis markers in EPCs. The results of in vivo experiments showed that ASCs combined with EPCs significantly promote the formation of blood vessels in the fat implant. Remarkably, EPCs may promote angiogenesis by paracrine regulation of endogenous endothelial cells (ECs) rather than direct participation in the formation of blood vessels.